Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan PT. Indofood Sukses Makmur Tbk - Budi Dharma; Dwy Franadita; Raihan Sultani (Universitas Labuhanbatu, 2023)
PT Indofood Sukses Makmur Tbk (INDF) produces sack flour, seasonings, beverages, packaging, cooking oil, processed foods, and condiments. In 1990, the company started doing business. The increase in sales is the basis for evaluating financial performance. Indofood has evolved into a full-service food solutions provider over the years, handling everything ready to sell. It is seen in the reports that show how over time, the financial performance of the business varies. Financial statements is the name given to these reports. Examination of the relationship of things in the budgetary summary or called fiscal summary investigation is essential for the monetary report to be significant to the individuals closely involved. Based on the analysis of the range of profits, the ability to meet debt repayment obligations, and debt repayment obligations, this study aims to determine whether Indofood Sukses Makmur Tbk (INDF) has sufficient capacity to guarantee and take care of obligations to banks and other business finances. the ability to meet debt repayment obligations may be used as a standard by investors when investing in an industry.